1984
DOI: 10.1152/ajpregu.1984.246.2.r184
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ovarian follicular growth and steroidogenesis by low-amplitude LH pulses

Abstract: A perifusion culture system controls the delivery of regulatory agents such that their concentration in the culture chamber is known at each and every point in time. The concentration in the culture chamber is predicted by the following equation: C(t) = Cf + (Ci - Cf)e(-R.t)/V, where C(t) is concentration in culture chamber (CC) at time t, Cf is concentration in holding flask (HF) (final CC concentration at t = infinity), Ci is initial CC concentration (t = 0), R is rate of media delivery from HF to CC (ml/h),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
“…More direct assessments of the role of pulsatile gonadotropin secretion on ovarian function have utilized perifusion systems. Peluso et al [26,27] observed that whole rat follicles secreted increased amounts of estradiol and had an increased proportion of mid-sized growing follicles when exposed to pulsatile versus tonic FSH stimuli. Furthermore, Peluso and Steger suggested that the effect of LH pulses given in the presence of a constant infusion of FSH depended on a threshold concentration of LH, as well as the rate of increase in LH concentrations [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies examining the importance of the pattern of hormonal stimulation on target organ response in several other hormonal systems have been reported. In perifused rat ovarian tissue, continuous administration of LH was less effective than pulsatile administration for supporting E 2 production (24). In humans treated with somatostatin to suppress endogenous insulin production, the hypoglycemic effect of administered insulin was greater during pulsatile compared to continuous delivery (25).…”
Section: Discussionmentioning
confidence: 93%
“…This interpretation is consistent with Foradori et al (2013), who showed GnRH pulse frequency was altered by high doses of ATR when administered by gavage. Although follicle recruitment had begun before the first ATR exposure, disruption of GnRH pulse frequency in some bolus-treated animals might have led to reduced follicle maturation (Peluso et al, 1984; Gong et al, 1996). In contrast, administration of ATR in the diet to SD or LE rats did not suppress the LH surge and did not have any effect on the number of CL or ova.…”
Section: Discussionmentioning
confidence: 99%